Evaluation of the inverse electron demand Diels-Alder reaction in rats using a scandium-44-labelled tetrazine for pretargeted PET imaging - Patricia E. Edem; Jean-Philippe Sinnes; Stefanie Pektor; Nicole Bausbacher; Raffaella Rossin; Abdolreza Yazdani; Matthias Miederer; Andreas Kjær; John F. Valliant; Marc S. Robillard; Frank Rösch; Matthias M. Herth (EJNMMI Research, 2019)
Abstract Background Pretargeted imaging allows the use of short-lived radionuclides when imaging the accumulation of slow clearing targeting agents such as antibodies. The biotin-(strept)avidin and the bispecific antibody-hapten interactions have been applied in clinical pretargeting studies; unfortunately, these systems led to immunogenic responses in patients. The inverse electron demand Diels-Alder (IEDDA) reaction between a radiolabelled tetrazine (Tz) and a trans-cyclooctene (TCO)-functionalized targeting vector is a promising alternative for clinical pretargeted imaging due to its fast reaction kinetics. This strategy was first applied in nuclear medicine using an 111In-labelled Tz to image TCO-functionalized antibodies in tumour-bearing mice. Since then, the IEDDA has been used extensively in pretargeted nuclear imaging and radiotherapy; however, these studies have only been performed in mice. Herein, we report the 44Sc labelling of a Tz and evaluate it in pretargeted imaging in Wistar rats. Results 44Sc was obtained from an in house 44Ti/44Sc generator. A 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA)-functionalized tetrazine was radiolabelled with 44Sc resulting in radiochemical yields of 85–95%, a radiochemical purity > 99% at an apparent molar activity of 1 GBq/mmol. The 44Sc-labelled Tz maintained stability in solution for up to 24 h. A TCO-functionalized bisphosphonate, which accumulates in skeletal tissue, was used as a targeting vector to evaluate the 44Sc-labelled Tz. Biodistribution data of the 44Sc-labelled Tz showed specific uptake (0.9 ± 0.3% ID/g) in the bones (humerus and femur) of rats pre-treated with the TCO-functionalized bisphosphonate. This uptake was not present in rats not receiving pre-treatment (< 0.03% ID/g). Conclusions We have prepared a 44Sc-labelled Tz and used it in pretargeted PET imaging with rats treated with TCO-functionalized bisphosponates. This allowed for the evaluation of the IEDDA reaction in animals larger than a typical mouse. Non-target accumulation was low, and there was a 30-fold higher bone uptake in the pre-treated rats compared to the non-treated controls. Given its convenient half-life and the ability to perform positron emission tomography with a previously studied DOTA-functionalized Tz, scandium-44 (t 1/2 = 3.97 h) proved to be a suitable radioisotope for this study.